The Politics and Metapolitics of Left-Wing Decline and Revival - Huijzer, M. Jouke (Frontiers in Political Science, 2022)
Conventional studies on left-wing decline focus primarily on the electoral losses of left-wing parties. This contribution argues that left wing decline should not only be understood in terms of support, but also in terms of ideological positioning. The Left may be in decline because of electoral support or because left-wing parties cease to be Left. More fundamentally the Left may be in decline because left-wing ideologies no longer inform public policy or shape political conflict, which points to a more metapolitical shift in “hegemonic ideology”. Taking this into account has important implications for understanding Left decline (and eventual revival). As will be demonstrated in six different scenarios, the Left may decline because of electoral shifts to the right or because parties reposition themselves to the right. Reviving the Left therefore not only implies that Left-wing parties win back voters, but it can also be achieved on a so-called metapolitical level: by shifting ideological positions or even hegemonic ideology to the Left. It is argued that especially with regard to shifting ideological positions, smaller parties in the political margins play a crucial role. The article concludes by discussing the implications and challenges for different political parties as well as the way in which political scientists can more comprehensively assess Left decline.